Cancer and Aging: Reflections for Elders (CARE): A pilot randomized controlled trial of a psychotherapy intervention for older adults with cancer. Issue 1 (7th November 2018) - Nelson, Christian J.; Saracino, Rebecca M.; Roth, Andrew J.; Harvey, Elizabeth; Martin, Anne; Moore, Mark; Marcone, Dana; Poppito, Shannon R.; Holland, Jimmie
Abstract: Objective: Cancer and Aging: Reflections for Elders (CARE) is a novel, telephone‐delivered intervention designed to alleviate distress in older cancer patients. This pilot randomized controlled trial tested the feasibility and initial efficacy of CARE, drawing from age‐appropriate developmental themes and well‐established coping theory. Method: Eligible patients were ≥70 years old; ≥6 months post‐diagnosis of lung, prostate, breast, lymphoma, or gynecological cancer; on active cancer treatment or within 6 months of ending cancer treatment; and had elevated scores on the Distress Thermometer (≥4) or Hospital Anxiety and Depression Scale (≥6). Participants completed five sessions of psychotherapy over 7 weeks with assessments at study entry, post‐intervention, and 2 months post‐intervention. Primary outcomes were feasibility and initial efficacy on anxiety and depression; secondary outcomes included demoralization, coping, loneliness, and spiritual well‐being. Results: Fifty‐nine participants were randomized to either the CARE arm (n = 31) or the enhanced Social Work Control arm (n = 28). The intervention was feasible and tolerable, meeting a priori criteria for rates of eligibility, acceptance, retention, assessment, and treatment fidelity. Upon completion of the intervention, participants in the CARE arm demonstrated lower mean depression scores ( d = 0.58 [CI: 0.04‐1.12], P = 0.01) and trended towards increased coping‐planning ( d = 0.30 [CI: −0.83 to 0.24], P = 0.18). Promising trends in anxiety ( d = 0.41 [CI: −0.17 to 0.98], P = 0.10) emerged at 2 months post‐intervention; effects for coping‐planning dissipated. Conclusion: These pilot data suggest the CARE intervention is feasibly delivered, potentially impacts important psychosocial variables, and is accessible for older, frail patients with cancer. Future research will evaluate this intervention on a larger scale.